A Place to Be : Brazilian, Guatemalan, and Mexican Immigrants in Florida's New Destinations - Vásquez, Manuel A.; Steigenga, Timothy J., 1965-; Williams, Philip J., 1959- (Book collections on Project MUSE., 2009)
A Place to Be is the first book to explore migration dynamics and community settlement among Brazilian, Guatemalan, and Mexican immigrants in America's New South. The book adopts a fresh perspective to explore patterns of settlement in Florida, including the outlying areas of Miami and beyond. The stellar contributors from Latin America and the United States address the challenges faced by Latino immigrants, their cultural and religious practices, as well as the strategies used, as they move into areas experiencing recent large-scale immigration.